Rengget dan Ratapan Moltmann: Mengeksplorasi Model Ratapan Karo dan Jürgen Moltmann - Joice Ria br Sitepu (Indonesian Journal of Theology, 2026)
This article argues that, in the face of suffering, humans attempt to find patterns formed by certain interests, whether in the effort to survive or to find meaning. This article discusses rengget (a chant of the Karo people) and two ideas from Moltmann concerning the languages of lamentation as responses to suffering. By imagining Moltmann lamenting through his work, the two techniques are placed side by side as models of lamentation in an effort to understand theodicy. Rengget, as a cultural product, is an instrument that nurtures relationships, memories, and hopes. Moltmann’s works point to the meaning of hope. These two models of lamentation converge on the idea of the interconnectedness of all things. The convergence of rengget and Moltmann’s lamentation offers a way to theologically reflect on suffering and theodicy.